Game-Boards and Gaming-Pieces in Funerary Contexts in the Northern European Iron Age - Whittaker, Helène (Nordlit, 2006)
Gaming-pieces, dice, and game-boards are found in connection withburials at various times and places from an early date. For instance, inEgypt there was a clear association between the game known as Senetand burials from the time of the Old Kingdom (Pusch 1979; Piccione1984). Dice are not uncommonly found in Greek, Etruscan, and Romantombs (Vermeule 1979, 80; Pallottino 1955, fig. 95; Egidi 1983). It canreasonably be assumed that the playing of board games was seen as apleasurable pastime which one could hopefully continue to pursue inthe Afterlife. However, it can in some cases be argued that gamingequipment in burial contexts was related to the social status of the deceased or to religious beliefs and therefore had a more complex significance. In this article I will look at the occurrence of gaming-pieces,dice, and game-boards in burials in the northern European Iron Age.